Avaliando a efetividade da Lei Maria da Penha - Daniel Cerqueira; Mariana Matos; Ana Paula Antunes Martins; Jony Pinto Junior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The Law 11.340, known as Maria da Penha Law (MPL), enacted in 2006, represented an important institutional framework in order to overcome domestic violence in Brazil. However, more than eight years after the sanction of MPL, there is a complete gap about empirical studies to evaluate their effect, which is the object of this work. We Constructed a model of differences in differences, where homicides against women that occurred at home were compared with those against men. Our results indicated that the law played an important role to curb gender violence, although its effectiveness has potentially been heterogeneous between localities due to different level of institutionalization of the protective service to victims, described by the law.
Keywords: K42; 330; Maria da Penha Law; evaluation; Brazil; domestic violence